Dynamic quorum policy for maximizing throughput in limited information multiparty MAC - Chaporkar, P.; Sarkar, S.; Shetty, R. (IEEE/ACM transactions on networking, 2006)
In multiparty MAC, a sender needs to transmit each packet to a set of receivers within its transmission range. Bandwidth efficiency of wireless multiparty MAC can be improved substantially by exploiting the fact that several receivers can be reached at the MAC layer by a single transmission. Multiparty communication, however, requires new design paradigms since systematic design techniques that have been used effectively in unicast and wireline multicast do not apply. For example, a transmission policy that maximizes the stability region of the network need not maximize the network throughput. Therefore, the objective is to design a policy that maximizes the system throughput subject to maintaining stability. We present a sufficient condition that can be used to establish the throughput optimality of a stable transmission policy. We subsequently design a distributed adaptive stable policy that allows a sender to decide when to transmit using simple computations. The computations are based only on limited information about current transmissions in the sender's neighborhood. Even though the proposed policy does not use any network statistics, it attains the same throughput as an optimal offline stable policy that uses in its decision process past, present, and even future network states. We prove the throughput optimality of this policy using the sufficient condition and the large deviation results. We present a MAC protocol for acquiring the local information necessary for executing this policy, and implement it in ns-2. The performance evaluations demonstrate that the optimal policy significantly outperforms the existing multiparty schemes in ad hoc networks